IMPLEMENTASI MEDIA VISUAL INFOGRAFIS MATERI SIFAT-SIFAT KUBUS TERHADAP HASIL BELAJAR SISWA KELAS V - Meiningtias, Riska; Wicaksono , Vicky Dwi; Supardal, Yaqobus; Rahayu, Oikida; Nailun Najah, Novianis Muhammi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to improve class V learning outcomes at SDN KUDU 1 Kertosono regarding the properties of cubes. This research uses observation in each cycle. There are two cycles used. The subjects in this research were class V students at SDN KUDU 1 Kertosono, consisting of 10 students. This research was conducted because there were obstacles in the material on the properties of cubes in class V. The teacher did not use media in the learning process, so that in the learning process students were less interested, not conducive, did not understand the material and were passive. When using this infographic visual media in cycle II there was a significant increase in learning outcomes for class V students. This was proven by the results of observations in cycle I, the percentage of student completion was 30% and in cycle II it was 90%. The conclusion that can be drawn from this research is that the implementation of infographic visual media on cube properties material can improve the learning outcomes of class V students at SDN KUDU 1 Kertosono.